INOVASI APLIKATIF PEMANFAATAN PLATFORM KLAMPID NEW GENERATION DALAM MENJAMIN KUALITAS LAYANAN ADMINDUK DI KOTA SURABAYA - Thoyyibah, Roihatut; Eprilianto, Deby Febriyan (Publika, 2024)
The Population and Civil Registration Office of Surabaya City created the Klampid New Generation innovation to facilitate administrative services for the community, which can be accessed independently or with assistance from District and Village operators. However, independent submissions are still quite low because people do not understand how to operate it and people are still comfortable making submissions through intermediaries of District and Village operators. This study aims to analyze the quality of population administration services through the KNG application. The research method used is descriptive with a qualitative approach, based on six dimensions of e-Government service quality (E-GovQual) from Papadomichelaki and Mentzas (2012) namely ease of use, trust, environmental interaction functions, reliability, content and appearance, and citizen support. Data analysis techniques include data collection, data reduction, data presentation, and conclusion drawing. The results showed that ease of use was met quite well with a simple and memorable website structure, although information on document requirements was not yet available. Trust is fulfilled quite well with adequate privacy and security protection, although without written consent. The interaction function of the environment shows adequate form filling assistance, but the online response format is missing. ervice reliability is met with good accessibility and timeliness of delivery. Website content and appearance are simple and easy to use, although information on requirements is not available in every menu. Citizen support showed responsive and knowledgeable staff, but contact information could be improved. The research suggests adding document requirement information in each menu and contact information, registering the application in the playstore and appstore, providing written consent for users, and updating the appearance of the application to improve the effectiveness and efficiency of KNG services.